Revolution and leadership a study of four countries - Entessar, Tahmineh (Ann Aror, Mich. UMI Dissertation Information Service, 1983)
Study of the revolutionary leadership of Sukarno, Mao Tse-tung, Gamal Abdel Nasser, and Vladimir Ilich Lenin.
Vita
Thesis (Ph. D.)--Saint Louis University, 1983.
Includes bibliographical references (leaves 290-311)
Keywords: Soekarno -- 1901-1970.; Nasser, Gamal Abdel -- 1918-1970.; Mao, Zedong -- 1893-1976.; Lenin, Vladimir Ilich -- 1870-1924.; Revolutions -- Case studies; Revolutions -- Indonesia -- History; Revolutions -- China -- History; Revolutions -- Egypt -- History; Revolutions -- Soviet Union -- History; Leadership; Communist leadership -- China; Communist leadership -- Soviet Union; Indonesia -- History -- Revolution, 1945-1949.; China -- History -- Republic, 1912-1949.; China -- History -- Civil War, 1945-1949.; Egypt -- History -- Revolution, 1952.; Soviet Union -- History -- Revolution, 1917-1921.